Impact of nutritional status on pulmonary function after lung transplantation for cystic fibrosis. Issue 7 (August 2018) - Staufer, Katharina; Halilbasic, Emina; Hillebrand, Peter; Harm, Solveig; Schwarz, Stefan; Jaksch, Peter; Kivaranovic, Danijel; Klepetko, Walter; Trauner, Michael; Kazemi-Shirazi, Lili
Background: Nutritional status is an important prognostic factor in patients with cystic fibrosis (CF) prior to lung transplantation. Objective: To investigate the impact of nutritional status on pulmonary function in CF transplant recipients. Methods: Adult double lung transplanted CF patients were consecutively included. The predictive value of nutritional status on lung function – measured by spirometry – was longitudinally assessed by body composition serially evaluated by a three-compartment model bioelectrical impedance analysis (BIA) in comparison to body mass index (BMI). Results: Overall, 147 spirometries and 147 BIAs were performed in 58 patients (59% female, median age: 30.1 years, median BMI: 19.6 kg/m 2 ). Malnourished patients (BMI < 18.5 kg/m 2 ; 27.6%) had a significantly reduced lung function compared to normal/overweight patients (forced expiratory volume in 1 second in percent (FEV1%pred), 57% vs 77%; p  = 0.024). BMI, as well as the BIA parameters phase angle, total body water, fat free mass, body cell mass (BCM) and extracellular mass (ECM)/BCM ratio, were univariate predictors of FEV1%pred. When included in a linear mixed model, ECM/BCM ratio remained the only significant predictor of lung function ( p  = 0.012). Conclusion: Nutritional status assessed by BIA predicted lung function in CF transplant recipients. Serial BIA measurements to monitor patients' nutritional status might help to improve or maintain lung function.